2016
DOI: 10.1007/s10695-016-0297-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary yeast inclusion and acute stress on post-prandial whole blood profiles of dorsal aorta-cannulated rainbow trout

Abstract: Yeast is a potential alternative to fish meal in diets for farmed fish, yet replacing more than 50 % of fish meal results in reduced fish growth. In a 4-week experiment, 15 rainbow trout (Oncorhynchus mykiss) were cannulated and fed three diets each week: 30 % fish meal as a control (FM); 60 % replacement of fish meal protein, on a digestible basis, with Saccharomyces cerevisiae (SC); and 60 % replacement with Wickerhamomyces anomalus and S. cerevisiae mix (WA). Blood was collected at 0, 3, 6, 12 and 24 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 72 publications
(83 reference statements)
3
19
0
Order By: Relevance
“…The tip of the villi are normally hypoxic, but the hypoxic area can extend further down in the villi during neutrophil infiltration and/or decreased blood perfusion of the intestine (Colgan & Taylor, ). Huyben et al () who fed rainbow trout the same diets as in the present study found that fish fed the yeast‐based diets displayed signs of haemolytic anaemia. Those authors suggested that high levels of nucleic acids in yeast‐based diets could overwhelm anti‐oxidative processes and impair red blood cells, consequently leading to cell lysis, and recommended limited use of yeasts in fish diets.…”
Section: Discussionsupporting
confidence: 64%
“…The tip of the villi are normally hypoxic, but the hypoxic area can extend further down in the villi during neutrophil infiltration and/or decreased blood perfusion of the intestine (Colgan & Taylor, ). Huyben et al () who fed rainbow trout the same diets as in the present study found that fish fed the yeast‐based diets displayed signs of haemolytic anaemia. Those authors suggested that high levels of nucleic acids in yeast‐based diets could overwhelm anti‐oxidative processes and impair red blood cells, consequently leading to cell lysis, and recommended limited use of yeasts in fish diets.…”
Section: Discussionsupporting
confidence: 64%
“…; Huyben et al . ), although the highest gut pH was found in fish fed FM in cold water (i.e. 8·51) and suggests that the buffering capacity of FM was impaired at lower temperatures while yeast was unaffected.…”
Section: Discussionmentioning
confidence: 94%
“…6). Previous studies have found that FM has a higher buffering capacity than yeast (Montanez-Valdez et al 2013;Huyben et al 2017b), although the highest gut pH was found in fish fed FM in cold water (i.e. 8Á51) and suggests that the buffering capacity of FM was impaired at lower temperatures while yeast was unaffected.…”
Section: Diet and Temperature Effects On Gut Bacterial Compositionmentioning
confidence: 88%
“…This study was part of a larger study that investigated whole blood and cortisol parameters after feeding fish meal‐ and yeast‐based diets to rainbow trout and contains more information on tank design, DA cannulation and blood sampling methods, see Huyben et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…The study was performed in compliance with laws and regulations on the use of animals for research purposes in Sweden, which is overseen by the Swedish Board of Agriculture (permit reference C74-14). This study was part of a larger study that investigated whole blood and cortisol parameters after feeding fish meal-and yeast-based diets to rainbow trout and contains more information on tank design, DA cannulation and blood sampling methods, see Huyben et al (2016).…”
Section: Fish and Facilitiesmentioning
confidence: 99%